Outdoor recess is associated with more positive attitudes toward physical activity among pre-adolescent students and their parents - Lemberg, Getter Marie; Kull, Merike; Mäestu, Jarek; Riso, Eva-Maria; Mägi, Katrin; Mäestu, Evelin (Frontiers in Sports and Active Living, 2024)
Introduction School day structure has the potential to increase students’ physical activity (PA) levels and form positive attitudes about PA. Including various PA opportunities and free play possibilities in the school schedule, especially outdoor recess, can improve students’ moderate-to-vigorous PA (MVPA) levels during school time. Therefore, the main aim of the study was to investigate students’ and their parents’ attitudes about outdoor recess and PA opportunities in schools with different recess opportunities. Methods Students from grades three to six (9–13-year-olds) and their parents responded to a questionnaire about the effect of outdoor recess and opportunities for PA during the school day. Schools were divided into three groups based on the recess opportunities during the school day: (1) “outdoor recess”, (2) “outdoor recess on some days”, (3) “indoor recess”. Results Students and parents of the “outdoor recess” group had significantly more positive attitudes about outdoor recess and PA opportunities in school. Students of the “outdoor recess” group stated being significantly more active during their leisure-time compared to other groups. Parents of the “outdoor recess” group stated that the school has asked their opinion regarding PA opportunities during the school day significantly more compared to the other two groups. Discussion These findings emphasize the positive effect outdoor recess can have on students’ PA beliefs and habits. Parents of the “outdoor recess” group also had more positive attitudes toward PA which is important as parents most likely convey their attitudes and beliefs to their children. In addition, involving and informing parents is critical when changing the school schedule and introducing new school culture, to make the changes last.